M2 Macrophages Enhance Pathological Neovascularization in the Mouse Model of Oxygen-Induced Retinopathy - Yedi Zhou; Shigeo Yoshida; Shintaro Nakao; Takeru Yoshimura; Yoshiyuki Kobayashi; Takahito Nakama; Yuki Kubo; Kohta Miyawaki; Muneo Yamaguchi; Keijiro Ishikawa; Yuji Oshima; Koichi Akashi; et al. (2015)
Purpose: To investigate the roles played by M2 macrophages in a mouse model of oxygen-induced retinopathy (OIR). Methods: Oxygen-induced retinopathy was induced in C57BL/6J mice by exposing postnatal day seven (P7) pups to 75% oxygen and then returning them to room air at P12. Real-time RT-PCR and immunofluorescence staining were used to assess the levels and distributions of different macrophage markers. Bone marrow–derived M1 and M2 macrophages and mannosylated clodronate liposomes (MCLs) were injected into the vitreous on P12 to examine the effects at P17. M2 macrophages were cocultured with human retinal endothelial cells (HRECs) to examine their effects on proliferation and tube formation. Results: The results showed that the M2 macrophages, rather than M1 phenotype, were highly expressed in OIR mice. The number of M2 macrophages had increased significantly at P17, and the increase was closely associated with the presence of neovascular tufts in the OIR retinas. Selective depletion of M2 macrophages suppressed the pathological neovascularization and promoted physiological revascularization. In contrast, intravitreal injection of bone marrow–derived M2 macrophages or the culture supernatants promoted pathological neovascularization and inhibited physiological revascularization. In an in vitro coculture system, M2-polarized macrophages significantly promoted proliferation and tube formation of HRECs. Conclusions: These results indicated that M2 macrophages, rather than M1, play an important role in promoting retinal pathological neovascularization probably by producing secreted factors. Thus, targeting M2 macrophages could be a potential therapeutic option for inhibiting retinal pathological neovascularization.